Initiating the EFL University Students' Critical Thinking in Oral Mode through Pragma-Stylistic Strategies - Ruqoyyah Amilia Andania; Mohammad Romadhoni; Fatma Rahayu Nita; Slamet Setiawan; Ai-Chun Yen (Journal of Pragmatics Research, 2024)
Critical Thinking (Hereafter, CT) significantly correlates to the EFL students' speaking ability; students with high critical thinking perform better than students with low critical thinking. Several strategies can be implemented for initiating CT in the classroom. One of them is using language style conveyed by the teachers. However, few studies concern about this pragma-stylistic usage in the teaching-learning process. Therefore, this current study aims to analyze (1) types of pragma-stylistics strategies used by teachers in initiating the EFL university students' CT in oral mode; (2) the ways teachers use pragma-stylistics strategies in initiating the EFL university students' CT in oral mode; and (3) the teachers' perception of the students' response towards initiating the CT in oral mode. Qualitative descriptive using Interview was conducted to collect the data. The result showed that teachers prefer using Assertive-Stating, Assertive-Suggesting, Directive-Advising and Prolepsis strategies to initiate students' CT in their speaking classroom. They implement those strategies through some activities during the class, such as giving stimulus (text, audio, and video) in a particular theme, conducting group discussions or speaking club, providing instructions or questions, and giving feedback. Besides, the teachers pointed out that most students positively respond to the strategies that they have utilized. The strategies effectively motivate and encourage the students to enhance their CT. Furthermore, this study suggests language teachers initiate their students' CT through the pragma-stylistic strategies mentioned. Finally, further researchers are expected to discuss the same field in more comprehensive scopes with different language skills.